Kecemasan pada Lansia dengan Hipertensi di Wilayah Puskesmas Tuntang: Anxiety in the Elderly with Hypertension in the Tuntang Health Center Area - Nailan Najuha; Suwanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2025)
Hypertension is one of the common health problems experienced by the elderly. The prevalence of hypertension sufferers in the elderly continues to increase from year to year. Being diagnosed with hypertension not only has an impact on the physical condition but also experiencing excessive anxiety about complications of the disease which can affect daily life. The purpose of this study was to describe of anxiety level in the elderly with hypertension at the Tuntang Health Center. The design of this study used quantitative design with an analytical descriptive approach. Sampling using purposive sampling obtained a sample of 85 respondents. Data collection using the Geriatry Anxiety Scale (GAS) instrument. Data analysis was carried out using univariate analysis tests displayed in frequency distribution. The results of the study found that elderly people with mild anxiety levels were 2 respondents (2.4%), moderate anxiety levels were 30 respondents (35.3%), and severe anxiety levels were 53 respondents (62.3%), Data analysis was carried out using univariate analysis tests. The results of this study were dominated by a high level of anxiety in 53 respondents (62.3%). It is hoped that officers from the health center can provide community education to the founders of hypertension about how to deal with anxiety experienced by respondents ABSTRAK Hipertensi merupakan salah satu masalah kesehatan yang umum dialami oleh lansia. Prevalensi penderita hipertensi pada lansia terus mengalami peningkatan dari tahun ke tahun. Terdiagnosa penyakit hipertensi tidak hanya berdampak pada kondisi fisik tetapi juga pada kondisi psikologis lansia, seperti kecemasan. Lansia dengan hipertensi sering mengalami kecemasan berlebihan terhadap komplikasi penyakit, yang dapat berpengaruh pada kehidupan sehari-hari. Tujuan dari penelitian ini untuk mengetahui gambaran tingkat kecemasan pada lansia dengan hipertensi di Puskesmas Tuntang. Desain penelitian ini menggunakan desain kuantitatif dengan pendekatan deskriptif analitik. Pengambilan sampel menggunakan purposive sampling didapatkan sampel sebanyak 85 responden. Pengambilan data menggunakan instrumen Geriatry Anxiety Scale (GAS), Analisis data dilakukan menggunakan uji analisis univariat ditampilkan dalam distribusi frekuensi. Hasil penelitian didapatkan lansia dengan tingkat kecemasan ringan sebanyak 2 responden (2,4%), tingkat kecemasan sedang sebanyak 30 responden (35,3%), tingkat kecemasan berat sebanyak 53 responden (62,3%). Hasil penelitian ini didominasi oleh tingkat kecemasan berat sebesar 53 responden (62,3%). Diharapkan tenaga kesehatan dari puskesmas dapat memberikan edukasi pada penderita hipertensi tentang cara menangani kecemasan yang dialami pada responden.